GAYA KEPEMIMPINAN KEPALA TK (STUDI DESKRIPTIF PADA SALAH SATU TK DI WILAYAH KECAMATAN TAKISUNG KABUPATEN TANAH LAUT) - Masliani; Ahmad Suriansyah; Ratna Purwanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Leadership is the peak of control in an organization, with the presence of a leader who can transform all activities optimally will facilitate the effectiveness and efficiency of all activities carried out together to achieve the agreed goals. In the realm of early childhood education, the leader in question is a kindergarten principal. The role of the kindergarten principal in the early childhood education environment is very important in creating a working atmosphere that supports the professional development of teachers. This study examines the leadership style applied by the kindergarten principal at TK Negeri in Takisung. The purpose of this study is to describe the leadership style, describe the partnership relationship between teachers and kindergarten principals and how the coaching and empowerment strategies carried out by the principals of TK Negeri Pembina Takisung and TK Al Ihsan Takisung. This study uses a qualitative approach with a case study design, where data is obtained through observation, in-depth interviews with principals and teachers, and related documentation. The validity of the data is guaranteed through source triangulation techniques. The results of the study show that the leadership style applied by the Principal of TK Negeri in Takisung, Tanah Laut Regency is a transformational leadership style. This style is reflected in his ability to inspire, motivate, and build collective commitment to positive change in the school environment.